Membangun Peran Nilai – Nilai Pancasila Untuk Menciptakan Generasi Muda Di Sekolah Dasar Yang Damai - Alvianita, Veti; Muharam, Muharam; Suhaeni, Suhaeni (Peneliti.net, 2023)
Local durian marketing in the Loji area is quite a lot of consumer interest because it has its own characteristics, namely sweet taste and distinctive fragrant smell. Marketing of other types of durian is marketed together with local durian, even though each durian has different qualities and characteristics. Another problem is that farmers or traders do not tell the type of durian being sold, therefore if there is another type of durian that has a less good quality, consumers will give a bad value to the local durian loji. The purpose of this study, which is to identify the internal and external factors in the marketing strategy of local durian loji, as well as analyze the priorities and alternatives that can be applied in marketing durian loji Karawang Regency, West Java. This research was conducted in two sub-districts, namely Tegalwaru and Pangkalan sub-districts of Karawang Regency, West Java. Determination of the location is done purposively or by deliberate means based on the presence of local durian garden loji. The method applied in this research is SWOT analysis, and data collection uses two methods, namely primary and secondary. The sampling technique in this study used purposive sampling technique. Based on the results of the IFAS and EFAS matrix calculations with scores of 3.69 and 3.77. In the QSPM matrix, a priority strategy is obtained, namely